The Late Roman settlement at Ysterni on the island of Paros and the Parian production of ‘Aegean’ type lamps - Preliminary results - Diamanti, Charikleia; Lamprakis, Anastasios (Rei Cretariae Romanae Fautorum Acta, 2024)
This paper presents the first results of our research concerning the excavations of the Ephorate of Antiquities of the Cyclades at the site of Ysterni on the island of Paros (Greece). These excavations revealed a settlement of the Late Antique period with three kilns, an oil or wine press and many other workshop facilities which produced, among others, lamps. Through this mass production of Parian lamps, the island of Paros emerges as a large and the only, yet, known center of the previously so-called 'Aegean lamp' type, offering important new typological and chronological information.